2014
DOI: 10.5545/sv-jme.2013.1046
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Visual System for Recognition of Erythema Migrans, an Early Skin Manifestation of Lyme Borreliosis

Abstract: Lyme borreliosis is the most common human tick-borne infectious disease in the northern hemisphere, occurring predominantly in temperate regions of North America, Europe and Asia. The disease's most frequent manifestation is erythema migrans, a skin lesion that appears within days to weeks of a tick bite. Early recognition of the lesion is important since it enables proper management and thus prevention of later consequences of the disease which can hamper normal life. In this article, a novel visual system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Čuk et al [31] reported accuracies in the range of 69.23% to 80.42% using classical machine learning methods whereas, Burlina et al [32] reported the best accuracy of 81.51% using ResNet50 architecture for the case of EM vs all classification problems. There was a common subset of images collected from the internet in both the dataset of Burlina et al [4] and our Lyme dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Čuk et al [31] reported accuracies in the range of 69.23% to 80.42% using classical machine learning methods whereas, Burlina et al [32] reported the best accuracy of 81.51% using ResNet50 architecture for the case of EM vs all classification problems. There was a common subset of images collected from the internet in both the dataset of Burlina et al [4] and our Lyme dataset.…”
Section: Resultsmentioning
confidence: 99%
“…The unavailability of public EM datasets as a result of privacy concerns of medical data may be the reason for the lack of extensive studies in this field. Čuk et al [31] proposed a visual system for EM recognition on a private EM dataset using classical machine learning techniques including naïve Bayes, SVM, boosting, and neural nets (not deep learning). Burlina et al [4] created a dataset of EM by collecting images from the internet and trained a CNN architecture ResNet50 as a binary classifier to distinguish between EM and other skin conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convolutional neural networks (DCNNs) are solutions to a wide variety of problems in computer vision, natural language processing and robotics. The use of DCNNs in the diagnosis of EM rashes has been investigated before, but these studies focus on the creation of the algorithm rather than it's implementation into a usable form [ [12], [13]].…”
Section: Introductionmentioning
confidence: 99%